THE DEVELOPMENT AND IMPLEMENTATION OF SECONDARY PREVENTION MEASURES FOR CORONARY ARTERY DISEASE - Riley, Robert Francis (Wake Forest University, 2013)
Heart disease, and in particular coronary artery disease (CAD), has long been one of the leading causes of death in the US. In order to reduce the morbidity and mortality from CAD, secondary prevention practice guidelines have been developed by the major cardiovascular societies in the US and abroad to provide a benchmark for the care of patients with CAD. Previous studies have shown that patients undergoing coronary artery bypass graft (CABG) surgery after an acute myocardial infarction are less likely to receive these secondary prevention measures at hospital discharge relative to similar patients undergoing percutaneous coronary interventions (PCI). Although adherence to guidelines-based therapy has been imperfect for both procedures, secondary prevention adherence rates at discharge have been improving over time, particularly as public reporting of hospital performance has been implemented. This thesis will focus on the development of these guidelines, trends in adherence to these recommendations in Washington State, and the challenges of using these endpoints as markers of the quality of health care delivery.
Keywords: adherence; coronary artery disease; guidelines; revascularization; secondary prevention